Innovations in Additive Manufacturing - Khan, M. Adam.; Jappes, J. T. Winowlin; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book presents the history, fundamentals, process development, applications, post-processing, and experimental results from additive manufacturing. The chapters cover surface treatments, modification, advancements in heat treatment, mechanical hardening and its effect on the material properties. This book also presents content on simulation, modeling, and optimization of materials processing and surface engineering techniques.
Section I: Introduction to additive manufacturing -- 1. Metal Additive Manufacturing: From History to Applications -- 2. Introduction to additive manufacturing -- Section II: Additive manufacturing and materials development -- 3. Challenges in additive manufacturing for metals and alloys -- 4. Laser additive manufacturing of aluminium matrix composites -- 5. Additive manufacturing of non-ferrous metals -- 6. Development and optimization study of Poly-Lactic Acid blended carbon particles by fused deposition modelling Method -- 7. Role of Additive manufacturing in Biomedical Engineering -- Section III: Post Processing and investigations on 3D built materials -- 8. Surface finishing post-treatments for additive manufactured metallic components -- 9. Surface treatments and surface modification techniques for 3D built materials -- 10. Surface Coatings and Surface modification techniques for additive manufacturing -- 11. Mechanical Testing of Additive Manufacturing Materials -- 12. Electrochemical corrosion behavior of heat treated Inconel 718 superalloy manufactured by direct metal laser sintering (DMLS) in 3.5% NaCl solution -- 13. Machinability of 3D Printed Materials -- 14. Challenges Involved in Framing Additive Manufacturing Standards. .
Keywords: Industrial engineering; Production engineering; Industrial and Production Engineering; Additive manufacturing